1997
DOI: 10.1002/(sici)1099-0720(199706)11:3<187::aid-acp446>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical Misremembering: John Dean is not Alone

Abstract: SUMMARYSurvey respondents were asked to provide knowledge responses to public events and names that occurred as long ago as the 1930s and as recently as the 1980s. Respondents made errors that reflect the use of semantic and lexical memory systems, and reconstructive processes based on a semantic theme. Errors, as well as correct responses, are affected by whether the events originally occurred during the transition phase (early teens to mid-twenties). Responses indicate that events that occur during the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Bahrick and his colleagues (Bahrick, 1983, 1984; Bahrick, Bahrick, & Wittlinger, 1975) have shown that neutral facts, such as the names of fellow college students, college streets, or college-learned Spanish vocabulary, are steadily forgotten for six years, and then, if still retained, preserved for decades to come. Along the same lines, Belli, Schuman, and Jackson (1997) found good retention after decades for newsworthy events such as the Tet Offensive, at least for participants for whom the event “defined” their generation. Neither of these studies examined whether respondents remembered the circumstances in which they learned of the event, making their relevance to the topic of flashbulb memories at best speculative.…”
mentioning
confidence: 77%
“…Bahrick and his colleagues (Bahrick, 1983, 1984; Bahrick, Bahrick, & Wittlinger, 1975) have shown that neutral facts, such as the names of fellow college students, college streets, or college-learned Spanish vocabulary, are steadily forgotten for six years, and then, if still retained, preserved for decades to come. Along the same lines, Belli, Schuman, and Jackson (1997) found good retention after decades for newsworthy events such as the Tet Offensive, at least for participants for whom the event “defined” their generation. Neither of these studies examined whether respondents remembered the circumstances in which they learned of the event, making their relevance to the topic of flashbulb memories at best speculative.…”
mentioning
confidence: 77%
“…The strongest existing questionnaire evidence comes from studies by Schuman, Belli, and Bischoping (1997) and Belli, Schuman, and Jackson (1997). Inserted into a longer survey interview were questions asking that a subset of the following events or people be identified: the WPA, the Holocaust, the Marshall Plan, Joe McCarthy, Rosa Parks, the Tet Offensive, the Village ofMylai, Woodstock, John Dean, Watergate, and Christa McAuliffe.…”
Section: Existing Questionnaire Studies Of Public Eventsmentioning
confidence: 99%
“…In conventional questionnaires the interviewing sequence may affect the likelihood of reporting non-normative events with respondents' recollections of more recent events impairing their ability to remember earlier occurrences (Belli et al 1997). By contrast in LHCs the iterative structure of the interview and the use of temporal landmarks help the respondents access and report memories on unexpected events (Yoshihama et al 2005).…”
Section: Family Timesmentioning
confidence: 99%